Inventarisasi Konsep Ekosistem Pariwisata Dalam Pengembangan Destinasi Wisata Berkelanjutan: Kasus Waduk Walahar, Kabupaten Karawang - Vincent Sylvester Leewellyn; Fitri Abdillah (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2020)
Development in tourism supposed to be development of tourism destinations. There are three main components of tourism destinations that play an important role in the development, which are: tourists, local people (hosts), and the destination itself. This study was designed to record the components of the tourism ecosystem in the Walahar Tourism Destination, Karawang Regency. Walahar is known as a culinary destination in Karawang Regency. This research is expected to produce a model for developing sustainable culinary tourism destinations. The research was compiled with a preliminary stage compiling a profile of all tourism potentials, attractions, and gastronomic tourism products, and the level of readiness of the local community, in the study area. The expected research result is the inventory of the ecosystem components involved in the Walahar culinary destination. The identification of the tourism subsystem in Walahar Village shows that only one of the twelve subsystems qualifies as a tourism destination. Therefore the development of Walahar as a tourism destination requires government’s effort. The development of Walahar as a destination also seems to be a solution to improve the quality of the environment by improving sanitation and environmental hygiene.